Direct Observation of Stable Negative Capacitance in SrTiO3@BaTiO3 Heterostructure. (16th December 2019) - Wang, Zhongyang; Li, Hongyu; Hu, Huiying; Fan, Yuqi; Fan, Runhua; Li, Baowen; Zhang, Jiaoxia; Liu, Hu; Fan, Jincheng; Hou, Hua; Dang, Feng; Kou, Zongkui; et al.
Abstract: Negative capacitance in ferroelectrics has seem remarkable progress in recent years. However, direct measurement of negative capacitance has so far been a challenge due to its instable characteristic in the electrostatic field. An ingenious method to design stable negative capacitance by dielectric resonance under high‐frequency alternating electric fields is demonstrated. The well‐pronounced dielectric resonance and electrical property in BaTiO3 /SrTiO3 (BT/ST) bulk ceramics consisted of epitaxial core–shell particles are studied. As the negative capacitance can be considered as an inductive behavior, the dielectric resonance of permittivity induced by a LC resonance can be occurred. The dielectric resonance can be described by the Lorentz model and explained by Fano‐like resonance of TO2 phonon in BT. In addition, lowest resonant frequency is observed at effective Curie temperature. Benefiting from negative capacitance in the BT/ST ceramics, both high permittivity and negative permittivity are accompanied with low losses around the resonant frequency, which is useful for developing capacitors and metamaterials. Significantly, this work will provide an initiative avenue to obtain explicit negative capacitance of ferroelectrics in the frequency spectrum. Abstract : BaTiO3 /SrTiO3 bulk ceramics consisting of epitaxial core–shell heterostructures give a feasible path for achieving stable negative capacitance by dielectric resonance. The high permittivity and negative permittivity achieved around dielectric resonance show the intriguing possibilities to increase capacitance and develop epsilon‐negative metamaterials.